2019
DOI: 10.3389/fphys.2018.01834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estrogen on Musculoskeletal Performance and Injury Risk

Abstract: Estrogen has a dramatic effect on musculoskeletal function. Beyond the known relationship between estrogen and bone, it directly affects the structure and function of other musculoskeletal tissues such as muscle, tendon, and ligament. In these other musculoskeletal tissues, estrogen improves muscle mass and strength, and increases the collagen content of connective tissues. However, unlike bone and muscle where estrogen improves function, in tendons and ligaments estrogen decreases stiffness, and this directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 109 publications
4
149
0
Order By: Relevance
“…A higher stiffness of the connective tissue is associated with performance parameters such as jump height [131]. Therefore, the risk of ligament injuries and the power performance of women with low oestrogen potentially increases [132]. As we pointed out in the Adaptations to Short-Term and Long-Term LEA section, for male athletes other than runners, evidence on BMD is less clear.…”
Section: Consequences For Performancementioning
confidence: 94%
“…A higher stiffness of the connective tissue is associated with performance parameters such as jump height [131]. Therefore, the risk of ligament injuries and the power performance of women with low oestrogen potentially increases [132]. As we pointed out in the Adaptations to Short-Term and Long-Term LEA section, for male athletes other than runners, evidence on BMD is less clear.…”
Section: Consequences For Performancementioning
confidence: 94%
“…Female athletes are 1.5 times more likely to sustain an Anterior Cruciate Ligament (ACL) injury5 and may be at a greater risk of incurring mild traumatic brain injuries (eg, concussion)6 when compared with male athletes. Importantly, hormonal fluctuations throughout the menstrual cycle may contribute to changes in injury-risk and performance 7…”
Section: An Evidence-base For Managing the Performance And Well-beingmentioning
confidence: 99%
“…[40][41][42] This may be due to the musculoskeletal changes associated with maturation, leading to poorer neuromuscular control and landing mechanics in female athletes. 43,44 As the majority of the athletes in the current study are female, this could also explain why our study found older adolescent athletes to be categorized as greaterrisk athletes. Our study cannot conclude a direct relationship between fatigued athletes who were female or older and ACL injury.…”
Section: Discussionmentioning
confidence: 77%